Visi, Misi, dan Tujuan Lembaga Pendidikan Islam - Nasution, Imam Wahyudi; Ritonga, Nurhayani; Aprianto, Iwan; J, Jamrizal (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The development of quality Islamic education is highly dependent on the alignment between vision, mission, and goals with the needs of learners and society. This demands managers of educational institutions to continuously evaluate and adjust in order for institutions to continue to exist and excel. Additionally, the success of Islamic educational institutions in molding a noble moral and knowledgeable generation is not independent of the involvement of all parties, ranging from educational personnel, learners, parents, to the wider community. This synergy must be embodied in the vision and mission of the institution so that educational goals can be optimally achieved. Islamic educational institutions require a clear vision, mission, and goals as a foundation in implementing a quality educational process oriented to Islamic values. A vision provides a long-term direction, a mission outlines a strategy for achieving it, and goals are concrete goals to be achieved. The latest scholarly opinions emphasize the importance of integration between Islamic values with contemporary challenges such as globalization, technology, and moral crisis.